Integrated Strategy for Sustainable Cattle Fever Tick Eradication in USA is Required to Mitigate the Impact of Global Change - Pérez de León, Adalberto A.; Teel, Pete D.; Auclair, Allan N.; Messenger, Matthew T.; Guerrero, Felix D.; Schuster, Greta; Miller, Robert J. (Frontiers in Physiology, 2012)
The ticks Rhipicephalus (Boophilus) annulatus and R. (B.) microplus, commonly known as cattle and southern cattle tick, respectively, impede the development and sustainability of livestock industries throughout tropical and other world regions. They affect animal productivity and wellbeing directly through their obligate blood feeding habit and indirectly by serving as vectors of the infectious agents causing bovine babesiosis and anaplasmosis. The monumental scientific discovery of certain arthropod species as vectors of infectious agents is associated with the history of research on bovine babesiosis and R. annulatus. Together, R. microplus and R. annulatus are referred to as cattle fever ticks (CFT). Bovine babesiosis became a regulated foreign animal disease in the United States of America (U.S.) through efforts of the Cattle Fever Tick Eradication Program (CFTEP) established in 1906. The U.S. was declared free of CFT in 1943, with the exception of a permanent quarantine zone in south Texas along the border with Mexico. This achievement contributed greatly to the development and productivity of animal agriculture in the U.S. The permanent quarantine zone buffers CFT incursions from Mexico where both ticks and babesiosis are endemic. Until recently, the elimination of CFT outbreaks relied solely on the use of coumaphos, an organophosphate acaricide, in dipping vats or as a spray to treat livestock, or the vacation of pastures. However, ecological, societal, and economical changes are shifting the paradigm of systematically treating livestock to eradicate CFT. Keeping the U.S. CFT-free is a critical animal health issue affecting the economic stability of livestock and wildlife enterprises. Here, we describe vulnerabilities associated with global change forces challenging the CFTEP. The concept of integrated CFT eradication is discussed in reference to global change.